2011
DOI: 10.1159/000327945
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex-Related Changes in Rat Brain Mitochondrial Function

Abstract: Aging is responsible for the decline in the function of mitochondria and their increase in size and number - adaptive mechanism to restore mitochondrial function. Estrogens increase mitochondrial function, especially in female rats. The aim of this study was to determine the age-related changes in rat brain mitochondrial function focusing on sex differences. Cellular and mitochondrial protein and DNA content, mitochondrial oxidative and phosphorylative function in male and female rat brain from four different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 39 publications
5
27
1
1
Order By: Relevance
“…This brain area depends considerably on mitochondrial functionality as documented by the large number of papers describing agerelated mitochondrial dysfunctions such as decreased rate of electron transfer in complex I and complex IV, decreased membrane potential, and increased content of macromolecular oxidized products (Bagh et al 2011;Frenzel et al 2010;Gilmer et al 2010;Guevara et al 2009Guevara et al , 2011Navarro and Boveris 2010;Navarro et al 2008). In this brain area, we found that AL rats presented an age-related increase in TFAM amount, which was not associated with an increase in mtDNA content, but with a mtDNA decrease.…”
Section: Discussionmentioning
confidence: 59%
“…This brain area depends considerably on mitochondrial functionality as documented by the large number of papers describing agerelated mitochondrial dysfunctions such as decreased rate of electron transfer in complex I and complex IV, decreased membrane potential, and increased content of macromolecular oxidized products (Bagh et al 2011;Frenzel et al 2010;Gilmer et al 2010;Guevara et al 2009Guevara et al , 2011Navarro and Boveris 2010;Navarro et al 2008). In this brain area, we found that AL rats presented an age-related increase in TFAM amount, which was not associated with an increase in mtDNA content, but with a mtDNA decrease.…”
Section: Discussionmentioning
confidence: 59%
“…S1), although no differences were measured in brain or in reduced and oxidized GSH (Table S1). Female rats have better mitochondrial capacity showing less oxidative stress generation based in estrogen levels (Borras et al, 2003;Guevara et al, 2011). Sex hormones have neuroprotective effects, which have also been shown to increase mitochondrial efficiency (Nilsen and Brinton, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria, known as the energy factory of the cell, adopt many other pivotal physiological functions in the brain and other tissues such as a playing a role as a Ca 2+ -sink, integrating apoptotic signaling, being the primary site of radical oxygen species (ROS) generation, and synthesizing steroids [52][53][54][55]. Depending on the functional requirements, mitochondria represent highly dynamic organelles which constantly change their structure and subcellular distribution in response to the different metabolic and pathological demands of the cell.…”
Section: Regulation Of Mitochondrial Structural Organization By Estrogenmentioning
confidence: 99%